PENGARUH DESAIN PRODUK DAN PROMOSI TERHADAP VOLUME PENJUALAN PADA INDUSTRI BATIK (Studi Pada Industri Batik di Kabupaten Sragen ) - Sri Padmantyo; Eko Purnomo (Benefit: Jurnal Manajemen dan Bisnis, 2013)
This study was aimed at analyzing the effect of product design and promotion on sales volume in the batik industry in Sragen. This study is expected to provide a material consideration in the determination of product design and promotion policies that can improve the company’s sales volume. This study took 50 companies in Sragen batik as the study sample. This study testedthree hypotheses. The first hypothesis says that the design of the products significantly influence sales volume, is supported. This study also supports the second hypothesis which says that the promotion of a significant effect on sales volume. The third hypothesis is that the design of the product and promotion are jointly significant effect on the volume of sales is also supported.